PERANCANGAN SISTEM APLIKASI E-POLICY UNTUK AGENT PADA KENDARAAN BERMOTOR - Ricky Prabowo (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
KSK Group is an investment holding company engaged in insurance. KSK group was first established on February 16, in 2001. KSK Group is a state-owned company that is neighbor, Malaysia. The purpose of this scheme is to help insurance companies in distributing information to customers relating to the value of premiums, insurance policies through agent/broker related insurance and provide a sense of comfort and security to the insurance agent in the policy-making process is fast, easy and accurate calculation of premiums. Methodology to be used is the SDLC. Application programming e-Policy for the agent that is made has a back office. Application programming e-policy to the insurance agent on PT.Kurnia using PHP as the programming language, MySQL as database, server Apache XAMPP contained in the program and Macromedia Dreamweaver for web design. This system uses the method of testing black box testing and white box testing. The results achieved in this paper is an application program for the creation of e-policy on PT.Kurnia Insurance agent who can provide convenience to its users in making customer data collection, simplify reporting, and printing reports. Keywords: KSK Group, E-Policy, Insurance